Lattice Field Theory with the Sign Problem and the Maximum Entropy Method - Imachi, M.; Shinno, Y.; Yoneyama, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
Although numerical simulation in lattice field theory is one of the most effective tools to study non-perturbative properties of field theories, it faces serious obstacles coming from the sign problem in some theories such as finite density QCD and lattice field theory with the θ term. We reconsider this problem from the point of view of the maximum entropy method.